2020
DOI: 10.9770/jesi.2020.8.1(23)
|View full text |Cite
|
Sign up to set email alerts
|

Causes of employee fluctuation and the need for stabilization in Slovak hotels

Abstract: The issue of fluctuation and personnel stabilization is a subject of discussion and study by several domestic and foreign authors. A typical situation in the Slovak labour market is a combination of factors for increasing demand for labour and a lack of qualified employees forcing hotel managers to internally change the perception of employees in terms of stability. The aim of the paper is to specify the causes of fluctuation and propose options for stabilizing the rate of turnover in the hospitality industry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Conversely, a few studies have confirmed that voluntary staff turnover can be explained by job opportunities available outside workers’ current hotel or better prospective job offers from other organisations. For instance, Vetráková et al (2020) found that factors affecting staff turnover are linked with new opportunities such as a better offer from another company or hotel or the prospect of a desirable job abroad. More specifically, attractive opportunities are the most important determinant of job change among hotel managers.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, a few studies have confirmed that voluntary staff turnover can be explained by job opportunities available outside workers’ current hotel or better prospective job offers from other organisations. For instance, Vetráková et al (2020) found that factors affecting staff turnover are linked with new opportunities such as a better offer from another company or hotel or the prospect of a desirable job abroad. More specifically, attractive opportunities are the most important determinant of job change among hotel managers.…”
Section: Resultsmentioning
confidence: 99%
“…Motivated individuals that manager evaluates them and have pre-set achievable goals are willing to work longer than individuals who are not driven. It is possible to hire motivated volunteer and the volunteer loose the motivation without managing and good cooperation [20]; [21].…”
Section: The Willingness To Work and Motivation Of Volunteermentioning
confidence: 99%